'I feel … I need to defend myself': Exploring the influence of social worker's attachment history on the social worker-client relationship. Issue 3 (8th September 2022) - Ash, Zoe; Grey, Ben
This paper offers a qualitative exploration of the influence of attachment patterns on individual social worker-client relationships. An attachment theory-informed IPA methodology is employed to gain insight into the experiences of three practicing social workers. The Adult Attachment Interview and Meaning of the Client interview (adapted version of the Meaning of the Child Interview) are used alongside Interpretive Phenomenological Analysis, triangulating findings and common themes. We found evidence of specific childhood experiences and dangers replayed in interactions with their client, albeit in an individualised and context-dependent rather than uniform way. Also, the dangers inherent in the institutional context of child protection work can intensify tensions from workers' past history, resulting in a more defensive and self-protective approach than might have been expected from considering the professional's childhood attachment relationships alone. Therefore, expectations of the professional-client relationships in this context should be realistic on what can be achieved, focussing less on transformation and 'certainty', and more on increasing awareness and capacity to tolerate difficult feelings arising from past history that may be elicited in the professional-client relationship.